Lie groups and lie algebras a physicist's perspective - Bincer, Adam M. (Adam Marian) (Oxford : Oxford University Press, 2013)
This text gives an introduction to group theory for physicists with a focus on lie groups and lie algebras.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Lie groups; Lie algebras